Impact of Coseismic Frictional Melting on Particle Size, Shape Distribution and Chemistry of Experimentally-Generated Pseudotachylite - Montheil, Leny; Toy, Virginia G.; Scott, James M.; Mitchell, Thomas M.; Dobson, David P. (Frontiers in Earth Science, 2020)
In natural friction melts, or pseudotachylties, clast textures and glass compositions can influence the frictional behaviour of faults hosting pseudotachylites, and are, in turn, sensitive to the processes involved in pseudotachyite formation. Quantification of these parameters in situations where the host rock composition and formation conditions are well-constrained, such as analogue experiments, may yield calibrations that can be employed in analysis of natural pseudotachylites. In this paper, we experimentally-generated pseudotachylites in granitoid rocks (tonalite and Westerly granite) at Pconf = 40 MPa and slip rates of ~ 0.1 m s-1, comparable to the conditions under which natural pseudotachylite is known to form in Earth’s upper crust. We find variations in both clast textures and glass compositions that reflect formation processes, and probably influence the frictional behaviour of similar natural faults hosting pseudotachylite. Quantification of particle size and shape distribution with a semi-automatic image analysis method, combined with analysis of glass and host-rock composition of these experimentally-generated pseudotachylites, reveals that the textures of pseudotachylite material evolved by combinations of (1) comminution, (2) heterogeneous frictional flash melting and (3) homogeneous (diffusive) clast melting and/or marginal decrepitation. Fractal dimensions of pseudotachylite-hosted clasts (D ~ 3) that are greater than those of marginal fragmented host rock particles (gouge, D ~ 2.4), reflect an increase of the intensity of comminution by slip localisation during a pre-melting phase. Chemical analyses demonstrate these pseudotachylite glasses were generated by frictional flash melting, where host rock phases melt individually. Biotite is the least resistant to melting, feldspar intermediate, and quartz is the most resistant. The peudotachylite glass generated in these experiments has an alkaline composition, depleted in SiO2 compared to the bulk host-rock, and shows heterogeneous compositions in a single sample related to proximity to host-rock minerals. The percentage contributions of host-rock phases to the melt, calculated by a mixing model, shows that glass compositions are dominated by plagioclase and biotite. Within the melt, margins of clasts were dissolved uniformly by diffusion and/or affected by marginal decrepitation, resulting in convex and round shapes with convexities averaging ~ 0.8 and circularities averaging ~ 0.65.